CHIMNEYS' INFLUENCE ON FIRE RISK OF SOLID WOOD STRUCTURES IN RESIDENTIAL BUILDINGS IN RURAL BALKAN SETTLEMENTS - Laban Mirjana; Cvetkovska Meri; Trombeva Gavriloska Ana; Dragancic Suzana; Lazarevska Marijana; Dzolev Igor (Vinca Inst Nuclear, 2021)
According to official fire statistics, chimney fires account for almost 20% of all fires that occur in family residential buildings every year in the Balkan region. The high temperature from the chimneys may have an influence on fire spreading to the wooden girders. The objective of the study was to gather and analyse data on timber structure fire incidents occurring in family residential buildings in lowland rural settlements in Serbia (2010-2014) and a mountain settlement in Montenegro (2007-2013) in order to determine the extent to which existing data can be used in fire risk assessment. Additionally, the chimney-timber floor heat transfer mech anism was investigated, namely, the time dependent temperature distribution in the cross-section of few types of mostly used chimneys and floor structures were analysed. This research illustrates how the lack of chimney maintenance and social vulnerability of the settlements (aged rural population with low incomes, living in many cases alone in old houses in areas with limited access to distance heating systems or piped gas) could influence the fire risk in timber structures in rural low land and mountain areas. It is shown that significant differences exist with respect to fire causation over time and the type of wooden structural elements – due to different temperature distribution in the cross-sections of the floor structure, both in lowland and mountain settlements
Keywords: chimneys; risk analysis; residential buildings